2009
DOI: 10.1002/yea.1671
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of NAD+ biosynthesis from the salvage pathway in Saccharomyces cerevisiae

Abstract: Nicotinamide adenine dinucleotide (NAD+) is synthesized via two major pathways in prokaryotic and eukaryotic systems: the de novo biosynthesis pathway from tryptophan precursors, or by the salvage biosynthesis pathway from either extracellular nicotinic acid or various intracellular NAD+ decomposition products. NAD+ biosynthesis via the salvage pathway has been linked to an increase in yeast replicative lifespan under calorie restriction (CR). However, the relative contribution of each pathway to NAD+ biosynth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 20 publications
2
40
0
Order By: Relevance
“…Yeast cells appear to produce NAD + predominantly via the NA/Nam salvage pathway during exponential growth (27) because standard growth media contain high concentrations (400 μg/l or ~ 3 μM) of niacin (NA and Nam) and budding yeast has a very efficient NA transporter Tna1 (Km for NA = ~ 1.7 μM) (17). Interestingly, although NR is an endogenous metabolite (28), standard yeast growth media do not contain NR because they do not support the growth of NAD + synthesis mutants defective in both de novo and NA/Nam salvaging (for example, the qns1 Δ mutant).…”
Section: Overview Of Nad+ Biosynthesismentioning
confidence: 99%
“…Yeast cells appear to produce NAD + predominantly via the NA/Nam salvage pathway during exponential growth (27) because standard growth media contain high concentrations (400 μg/l or ~ 3 μM) of niacin (NA and Nam) and budding yeast has a very efficient NA transporter Tna1 (Km for NA = ~ 1.7 μM) (17). Interestingly, although NR is an endogenous metabolite (28), standard yeast growth media do not contain NR because they do not support the growth of NAD + synthesis mutants defective in both de novo and NA/Nam salvaging (for example, the qns1 Δ mutant).…”
Section: Overview Of Nad+ Biosynthesismentioning
confidence: 99%
“…NMN is generated by phosphorylating nicotinamide riboside (NR), which is catalyzed by the kinase Nrk1 at the expense of ATP (9,10). It has been shown that yeast cells produce NAD ϩ predominantly via the NA/Nam salvage pathway during exponential growth (11). More recently, NR has been shown to be an efficient NAD ϩ precursor that contributes to the NAD ϩ pool and supports NAD ϩ -dependent reactions (9,10).…”
Section: Pyridine Nucleotides Nadmentioning
confidence: 99%
“…Electrospray ionization was performed in positive-ion mode. Intracellular concentration of NAD ϩ was calculated by taking the volume of a haploid BY4742 cell to be 70 m 3 , the volume of a kynurenine pathway-or salvage pathway-knockout cell to be 40 m 3 (23), and the A 600 of 0.1 to correspond to 0.7 ϫ 10 6 cells/ml. LC-MS analysis for QA.…”
Section: Strains and Plasmidsmentioning
confidence: 99%